2009
DOI: 10.1007/s11164-009-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Formation of p-terphenyl excited states in the ionic liquid methyltributylammonium bis[(trifluoromethyl)sulfonyl]imide: pulse radiolysis study

Abstract: Solutions of 80 mM benzophenone (BP) and up to 14 mM p-terphenyl (TP) in the ionic liquid methyltributylammonium bis[(trifluoromethyl)sulfonyl]imide (R 4 NNTf 2 ) have been investigated by nanosecond pulse radiolysis. The resulting transient absorption spectra of pulse-irradiated argon saturated solutions correspond to the formation of several intermediates derived from BP and TP: benzophenone radical anion [(C 6 H 5 ) 2 CO] •-(BP •-) converted after *20 ls into ketyl radicals (C 6 H 5 ) 2 C • OH (BP • H), a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Pulse radiolysis coupled with the time‐resolved UV‐vis spectrophotometry was performed using the INCT LAE 10 linear accelerator with typical electron pulses lengths of 7‐10 ns. A detailed description of the computer‐controlled experimental setup has been given elsewhere . The system consists of the 150‐W “quiet” xenon lamp (Hamamatsu E7536) with a suitable housing and a power supply, the Oriel MSH 301 monochromator with two switchable outputs (one for a R955 photomultiplier and the second one for the ANDOR ICCD camera—intensified charge coupled device) and the LeCroy WaveRunner 6051A oscilloscope with an internal memory of 16 Mb.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pulse radiolysis coupled with the time‐resolved UV‐vis spectrophotometry was performed using the INCT LAE 10 linear accelerator with typical electron pulses lengths of 7‐10 ns. A detailed description of the computer‐controlled experimental setup has been given elsewhere . The system consists of the 150‐W “quiet” xenon lamp (Hamamatsu E7536) with a suitable housing and a power supply, the Oriel MSH 301 monochromator with two switchable outputs (one for a R955 photomultiplier and the second one for the ANDOR ICCD camera—intensified charge coupled device) and the LeCroy WaveRunner 6051A oscilloscope with an internal memory of 16 Mb.…”
Section: Methodsmentioning
confidence: 99%
“…BP was used as a primary scavenger of electrons ( e presolv − / e solv − ) and excited states of the IL components, that is, ([MeBu 3 N] + )* and ([NTf 2 ] − )*. However, it was previously found that the energy transfer from the excited states of this IL is of minor importance …”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations